Colorectal cancer with synchronous distant metastases: rationale for cytoreductive surgery and its perspectives – a surgeons view - V. A. Aliyev; Yu. A. Barsukov; A. V. Nikolayev; R. I. Tamrazov; Z. Z. Mamedli; A. O. Atroshchenko; D. V. Kuzmichev (Тазовая хирургия и онкология, 2015)
A rationale for cytoreductive surgery in colorectal cancer patients with multiple liver metastases is discussed in the article. Not only does it improve their quality of life and prevent life-threatening complications, but also facilitates further systemic treatment. Symptomatic surgery (colostomies and bypass surgery) does not improve treatment outcome independent from additional treatment. Our results demonstrate that chemotherapy with 2 or more active drugs after cytoreductive surgery significantly improves treatment results. Rationale for the use of chemoradiotherapy in rectal cancer patients with synchronous distant metastases is demonstrated in the article.